Applying heuristics evaluation to improve the usability of malaysia accounting training management system - Zuraidah, Mat Harun; Azma, Abdullah; Gunaratnam, Kiriyadhatshini (IOP Publishing, 2020)
The website is a connection of communication between the organization and their customers. By using web applications customers can obtain information and deal with the organization. The user interface and the interface design of web-based application affect the interest and attention of the customers. The consideration of web navigation, web usability and web accessibility are compulsory to make a website was designed in a user-friendly format. This study aimed to evaluate system based on issues of interface design with focusing on human-computer interaction and user interface design which are error human handling and accessibility. The questionnaire based on questions from the User Interface Usability Evaluation (User Interface Usability Evaluation) was conducted to obtain feedback on the system developed. The findings and results of the questionnaire was used to assess whether the training management system design interface both in terms of handling and ease of access error information (error information handling and accessibility).